Natural Killer Cells in Multiple Sclerosis: Entering the Stage - Beliën, Jarne; Goris, An; Matthys, Patrick (Frontiers in Immunology, 2022)
Studies investigating the immunopathology of multiple sclerosis (MS) have largely focused on adaptive T and B lymphocytes. However, in recent years there has been an increased interest in the contribution of innate immune cells, amongst which the natural killer (NK) cells. Apart from their canonical role of controlling viral infections, cell stress and malignancies, NK cells are increasingly being recognized for their modulating effect on the adaptive immune system, both in health and autoimmune disease. From different lines of research there is now evidence that NK cells contribute to MS immunopathology. In this review, we provide an overview of studies that have investigated the role of NK cells in the pathogenesis of MS by use of the experimental autoimmune encephalomyelitis (EAE) animal model, MS genetics or through ex vivo and in vitro work into the immunology of MS patients. With the advent of modern hypothesis-free technologies such as single-cell transcriptomics, we are exposing an unexpected NK cell heterogeneity, increasingly blurring the boundaries between adaptive and innate immunity. We conclude that unravelling this heterogeneity, as well as the mechanistic link between innate and adaptive immune cell functions will lay the foundation for the use of NK cells as prognostic tools and therapeutic targets in MS and a myriad of other currently uncurable autoimmune disorders.